The Other Josquin - Enhanced Editions of 16th century music - van Berchum, Marnix (Septentrio Conference Series, 2014)
Conflicting and doubtful composer attributions are a common phenomenon in early musical repertories, but the problem is particularly acute with the output of Josquin des Prez (c. 1450-1521), the foremost musical authority figure of the 16th century. The matter is far from unambiguous; the problems of determining which pieces really are authentic is a veritable scholarly minefield in which academic opinion changes constantly. The Other Josquin has two goals: to contribute to musicological research and humanities computing by producing 40 online music editions of compositions dubiously ascribed to Josquin des Prez, using the CMME system for digital early music editions; and the semantic enrichment of the CMME web dataset in accordance with semantic web standards such as RDF-XML.